An intelligent system for hearing disorder detection using auditory evoked potential (AEP) signals - Islam, Md Nahidul; Norizam, Sulaiman; Rashid, Mamunur; Mahfuzah, Mustafa; Mohd Shawal, Jadin (2021)
Approximately 466 million people have different kinds of hearing impairment in the world, and 34 million are children. Brain-computer interfaces (BCIs) are systems that link the human brain to external technology, which is the best way to address these concerns. Auditory evoked potentials (AEPs) are a type of EEG signal which has been commonly employed to detect early hearing disorder.